Bioanalytical techniques using microfluidics and nanotechnology - Novotný, Jakub (Univerzita Pardubice, 2019)
This dissertation thesis deals with the development and application of new microfluidic devices and similar products. To achieve this, several different fabrication techniques had to be utilized. Produced this way were microfluidic chips, microfluidics-related devices as well as micro-particles. This thesis summaries information on the fabrication methods and contains a collection of publications written or co-written by the author.
Bioanalytické techniky s využitím mikrofluidiky a nanotechnologií
Keywords: mikrofluidika; mikrofabrikace; thiol-eny; glykoproteiny; nano-destičky; microfluidics; microfabrication; thiol-enes; glycoproteins; nano-platelets